Exploring Sex-Based Neuropsychological Outcomes in Pediatric Brain Cancer Survivors: A Pilot Study - Chiara Colliva; Veronica Rivi; Pierfrancesco Sarti; Isabel Cobelli; Johanna M. C. Blom (Diseases)
Background: The increasing survival rates among pediatric cancer patients underscore the critical need to understand the long-term psychosocial impacts of cancer treatments, such as cisplatin and carboplatin. While these treatments are lifesaving, they may pose risks to neurodevelopmental processes. Despite the substantial body of research highlighting cognitive impairments associated with cancer treatments, there remains a gap in understanding how these effects differ by sex. As sex differences could inform tailored interventions and support mechanisms for affected individuals, this pilot study aimed to examine the sex differences in neuropsychological outcomes in patients treated for brain cancer with cisplatin and/or carboplatin. Methods: Our study employed rigorous/structured neuropsychological assessments to evaluate executive functions in pediatric cancer survivors treated with cisplatin and/or carboplatin. We utilized the BRIEF and TOL tests to assess the key domains of executive function, including inhibitory control, cognitive flexibility, and problem-solving abilities. Additionally, psychosocial factors were evaluated using the Resiliency Scale to measure resilience and the PAT test to assess family psychosocial risk. Results: In our cohort of 17 patients, significant sex differences emerged, where males outperformed females in areas such as inhibitory control, impulse regulation, and strategic planning. Conclusions: These findings highlight the complexity of cognitive outcomes in pediatric cancer survivors. Understanding sex-specific differences is essential for developing tailored interventions that optimize cognitive and psychosocial outcomes. Future research should focus on larger cohorts and longitudinal studies to validate these findings and guide targeted interventions to improve survivorship outcomes.